ONLINE ASSESSMENT IN ENGLISH CLASSROOM: EFL TEACHERS’ PRACTICES AND CHALLENGES - Dicky Meiantoni; Wiyaka Wiyaka; Entika Fani Prastikawati (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The outbreak of Covid-19 pandemic makes many changes in the educational system. One of the changes is in the process of assessment that is conducted by the teachers. Online assessment becomes the demand for teaching and learning process. In EFL teaching context, the English teachers are also demanded to present an online assessment that meets the students’ needs. The practice of online assessment needs to be investigated to capture whether it runs well or not. In line with this case, this present study describes online assessment practices as well as the challenges faced by the EFL teachers. By conducting descriptive qualitative research, the writers observed the practices of online assessment in English teaching in a junior high school in Semarang. There are three English teachers participated in this study. To obtain the data, the writers used observation and semi-structured interview as the instruments of data collection. After the data was collected, it was analyzed and interpreted descriptively. The findings show that English teachers implemented some online assessment tools such as Google Classroom, What’s App, Google Form, and Zoom in online assessment practices during the English teaching and learning. During the implementation of online assessment, the EFL teachers found some challenges such as internet connection, the different level of students’ intelligence, students’ low motivation, and EFL teachers’ lack of computer skills. The findings of this study imply that online assessment practices need to be evaluated to have a better implementation. Further, the EFL teachers’ computer skills need to be improved to realize an exemplary practices of online assessment in English teaching and learning.